2020
DOI: 10.3168/jds.2020-18274
|View full text |Cite
|
Sign up to set email alerts
|

Early supplementation of Saccharomyces cerevisiae boulardii CNCM I-1079 in newborn dairy calves increases IgA production in the intestine at 1 week of age

Abstract: addition, the number of IgA-producing plasma cells were greater in both ileum (2.55 ± 0.40 cells/mm 2 ) and colon (3.03 ± 0.40 cells/mm 2 ) tissues for SCB calves compared with control (respectively 1.00 ± 0.40 and 0.60 ± 0.42 cells/mm 2 ). Endogenous IgA production in the gut of SCB calves was enhanced, which could make them less prone to pathogen intrusion. In addition, SCB calves had higher Lactobacillus and tended to have higher Faecalibacterium prausnitzii in the jejunum compared with control calves, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…One of the recent studies have proposed that supplementation with Saccharomyces cerevisiae increased the immune responsiveness of calves by increasing IgA concentration (Villot et al, 2020). Furthermore, Sun et al (2020) showed that Bacillus subtilis natto increased general performance by improving the ADG and feed efficiency, and advanced the weaning age of the calves.…”
Section: Discussionmentioning
confidence: 99%
“…One of the recent studies have proposed that supplementation with Saccharomyces cerevisiae increased the immune responsiveness of calves by increasing IgA concentration (Villot et al, 2020). Furthermore, Sun et al (2020) showed that Bacillus subtilis natto increased general performance by improving the ADG and feed efficiency, and advanced the weaning age of the calves.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that probiotics have a positive effect in reducing the susceptibility of calves to intestinal infections before weaning (Markowiak and Śliżewska, 2018;Mazloom et al, 2019;Plaza-Diaz et al, 2019). The anti-diarrheal function of MSP may be associated with its role in immunity (Inatomi et al, 2017;Villot et al, 2020). Concentrations of circulating immunoglobulins, especially those of IgG, IgM, and IgA, are important indicators of immune function (Crassini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these traditional probiotics, certain commensals reportedly induce intestinal IgA responses in mice and cows. 130 , 131 Yang et al reported that 11 B. ovatus strains isolated from humans could strongly induce IgA production in mice. 130 Notably, this effect does not depend on the colonizing order of these bacteria since the transfer of a multiplex cocktail of these bacterial strains significantly and consistently elevated IgA production in humanized mice.…”
Section: Possible Applications For Early-life Gm Regulation Via Igamentioning
confidence: 99%
“…enrichment in the jejunum, corresponding with the ability of IgA to enhance Lactobacillus colonization. 17 , 131 …”
Section: Possible Applications For Early-life Gm Regulation Via Igamentioning
confidence: 99%